Single camera analyses in studying patern-forming dynamics of player interactions in team sports - Duarte, R.; Fernandes, O.; Folgado, H.; Araujo, D. (Complex systems in Sport, 2014)
This chapter outlines a low-cost and straightforward method to reconstruct the players' movement displacement trajectories in the performance context using a single camera. The high values of accuracy and reliability, as well as its flexibility, suggest the possibility of using this method in a wide range of training and competitive performance settings. Special care is recommended with signal processing in which appropriate data filtering and short-term digitization training programmes should be undertaken to remove high-frequency content noise (i.e.human and instrumentation error) from the inherent performance variability. Obtaining positional data from players on-field performance allowed us to identify the pattern forming dynamics emerging from players' interactions during a three-versus-three sub-phase of association football near the scoring areas. A functional relevant order parameter was proposed based on previous qualitative examinations of collective movement data. Sudden transitions associated to qualitative behavioural changes were identified in this order parameter (i.e. distance from a single centroid to the defensive boundary-line) by the influence of two intertwined control parameters (i.e. the inter-centroid distance and relative stretch index).